RANCANG BANGUN SISTEM INFORMASI PENJUALAN MOBIL SECOND HAND (Studi Kasus : CV. Singgalang Motor) - Jannah, Amiratul; Farell, Geovanne (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
The promotion process and sales reports at CV Singgalang Motor are still done manually, so employees must promote through brochures and write sales report data in the report book, this can result in data loss and damage. Making reports in this way often causes problems, such as errors in writing customer data and the time required in the reporting process becomes longer. In addition, in the process of writing ordering data, calculation errors often occur so that the report generation becomes repetitive and the process becomes less effective. Based on these problems, the solution given is the Design and Build of a Second Hand Car Sales Information System using the PHP programming language and the CodeIgniter Framework which aims to facilitate the process of used car sales promotion and report generation. The system development method used in this design is the Waterfall Method, so this application is feasible and can be used for making computerized sales reports so that the manufacturing process becomes more efficient.